Low n-3 Long-Chain Polyunsaturated Fatty Acids in Newly Diagnosed Celiac Disease in Children With Preexisting Type 1 Diabetes Mellitus. Issue 2 (February 2015) - Tárnok, András; Marosvölgyi, Tamás; Szabó, Éva; Györei, Eszter; Decsi, Tamás
ABSTRACT: Objective: Fat malabsorption can occur in celiac disease (CD) owing to villus atrophy and inflammation of small intestinal mucosa. Abnormal fatty acid (FA) status of intestinal mucosa in children with CD was reported earlier. Previously we found significantly reduced availability of n-3 long-chain polyunsaturated fatty acids (n-3 LCPUFA) in children and young adults with type 1 diabetes mellitus (DM). The aim of this study was to investigate FAs in plasma lipid classes in children with newly diagnosed CD with or without preexisting DM. Methods: FA composition of plasma samples of children with untreated CD only (n = 20) and with preexisting DM (CDDM, n = 8) were compared with those of healthy controls (n = 21). Detailed analysis of phospholipid, triacylglycerol, and sterol ester FAs was performed by high-resolution capillary gas–liquid chromatography. Results: Significantly decreased docosapentaenoic (C22:5n-3), docosahexaenoic (C22:6n-3), n-3 polyunsaturated fatty acids (n-3 PUFA), and n-3 LCPUFA values were found in CDDM group compared with controls and patients with CD. When compared with healthy controls, no significant difference was found in plasma FAs of children with newly diagnosed CD only. Conclusions: Children with CDDM showed marked signs of reduced availability of n-3 PUFA and n-3 LCPUFA in circulating lipids. Although different tissues express membrane FAs differently, our present study suggests that CD on its own does not necessarily lead to detectable disturbances of essential FA metabolism in plasma and supports the concept that DM has significant impact on plasma FA composition in children.